NATIONAL VALUES AND THE DYNAMICS OF GENDER EQUALITY IN CONTEMPORARY UZBEKISTAN - Aziza Fozilova (Bright Mind Publishing, 2025)
This article examines the significance and role of national values in shaping gender equality within the family. Family relationships, formed on the basis of national traditions and culture, play a crucial role in ensuring equality between genders. The study analyzes both the encouraging and restrictive aspects of national values regarding gender equality and explores ways to strengthen gender equality within the family institution. Additionally, the necessity of harmonizing national values with gender equality in modern society is emphasized.
Keywords: National values, gender equality, family, family relations, gender equality, culture, society, gender education.